SIFАTLI TАЪLIM-DАVR TАLАBI - Nazarov, N.N. (Educational Research in Universal Sciences, 2023)
The article emphasizes the fact that improving the quality of education is the imperative of the times, and it is necessary to use modern methods to train mature staff of higher educational institutions.